Advances in Statistical Approaches to Oncology Drug Development. (January 2014) - Ivanova, Anastasia; Rosner, Gary L.; Marchenko, Olga; Parke, Tom; Perevozskaya, Inna; Wang, Yanping
The authors describe some recent developments in statistical methods and practice in oncology drug development from an academic and an industry perspective. Many adaptive designs were pioneered in oncology, and oncology is still at the forefront of novel methods to enable better and faster go/no-go decision making while controlling the cost.